Efficacy and safety of the type I interferon receptor inhibitor anifrolumab in patients with systemic lupus erythematosus (results of a 6-month study) - T. M. Reshetnyak; E. A. Aseeva; A. A. Shumilova; N. Yu. Nikishina; S. I. Glukhova; S. Yu. Shkireeva; A. M. Lila (Современная ревматология, 2024)
Objective: to evaluate the efficacy and safety of the type I interferon (IFN) receptor inhibitor anifrolumab (AFM, Safnelo®) in patients with systemic lupus erythematosus (SLE) in real-life clinical practice over an observation period of 6 months.Material and methods. The prospective 6-month study included 21 patients with SLE fulfilling the 2012 SLICC criteria, predominantly women (n=17,81%), median age – 31 [27; 46] years, disease duration – 9 [6.0; 11.0] years. Standard laboratory values and immunological markers of SLE were examined in all patients. The SLEDAI-2K index was used to determine the activity of SLE, and the severity of the mucocutaneous syndrome was assessed using the Cutaneous Lupus Disease Area and Severity Index (CLASI) index. Organ damage was assessed using the SLICC/ACR Damage Index (DI). After 6 months, the achievement of low activity was assessed according to the Lupus Low Disease Activity State (LLDAS) indexResults and discussion. At the time of inclusion in the study, the mean SLEDAI-2K activity index for the group was 8 [6.0; 10.0] points, the median CLASI index – 8.6±8.2 points, 81% of patients had skin and mucosal lesions, 66% had non-erosive polyarthritis, and high immunological activity was observed in all cases. Various irreversible organ damage was observed in 86 of patients. The average DI was 2.2±1.5 points. At the start of AFM therapy, all patients received glucocorticoids (GCs) at a mean dose of 10.7±5.6 mg/day, 52% of patients received a dose above 10 mg/day, 76% of patients continued to take hydroxychloroquine, and 33% of patients took immunosuppressants. Significant positive dynamics were observed with AFM therapy. The average CLASI index for the group after 3 months of treatment was 1.2±4.1 points, after 6 months – 0.3±1.2 points (p<0.0001). The SLEDAI-2K index fell significantly in the group on average from 8 [6.0; 10.0] to 2 [2.0; 4.0] points from the 3rd month of treatment (p<0.0001) and remained at the same level after 6 months. At month 6 of treatment, 13 (62%) of 21 patients met the LLDAS criteria for low disease activity. After the 3rd month of treatment, a significant decrease in antibodies against dsDNA was observed, which persisted for 6 months after the start of treatment. In the group as a whole, there were no significant changes in complement fractions values during the observation period. There was no increase in irreversible organ damage (DI – mean 2.2±1.5 points). The mean daily dose of GCs was significantly reduced from 10.7±5.6 mg/day to 7.5±4.0 mg/day (p<0.01) by the 3rd month and to 5.2±2.1 (p<0.001) by the 6th month of treatment. No infusion reactions were observed in any case. Adverse events occurred in 9 (42%) out of 21 patients, mainly herpes infections of varying severity, mainly after the 1st to 3rd infusions. In one case, severe herpes zoster was observed, so the drug was discontinued.Conclusion. At a dose of 300 mg intravenously monthly AFM is a highly effective drug with a relatively good safety profile in patients with active SLE in whom autoantibodies are present and who do not respond adequately to standard therapy.